2015
DOI: 10.1152/advan.00101.2014
|View full text |Cite
|
Sign up to set email alerts
|

Exercise, cognitive function, and aging

Abstract: Increasing the lifespan of a population is often a marker of a country's success. With the percentage of the population over 65 yr of age expanding, managing the health and independence of this population is an ongoing concern. Advancing age is associated with a decrease in cognitive function that ultimately affects quality of life. Understanding potential adverse effects of aging on brain blood flow and cognition may help to determine effective strategies to mitigate these effects on the population. Exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
176
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(193 citation statements)
references
References 58 publications
5
176
0
12
Order By: Relevance
“…Cognitive impairment is multifactorial, but a history of cigarete smoking, aging and educational level are recognized as major determinants [25,26]. The origin of the cerebral dysfunction COPD -An Update in Pathogenesis and Clinical Managementin patients with COPD is still unknown, assuming the interference of several pathological relays: hypoxemia, oxidative stress, systemic inlammation, smoking, comorbidities, vascularmediated brain pathology, neurotransmiter metabolism in the central nervous system (CNS), a decrease in physical functioning, genetic and epigenetic factors.…”
Section: Copd: Fundamental Pathophysiological Mechanisms Susceptible mentioning
confidence: 99%
“…Cognitive impairment is multifactorial, but a history of cigarete smoking, aging and educational level are recognized as major determinants [25,26]. The origin of the cerebral dysfunction COPD -An Update in Pathogenesis and Clinical Managementin patients with COPD is still unknown, assuming the interference of several pathological relays: hypoxemia, oxidative stress, systemic inlammation, smoking, comorbidities, vascularmediated brain pathology, neurotransmiter metabolism in the central nervous system (CNS), a decrease in physical functioning, genetic and epigenetic factors.…”
Section: Copd: Fundamental Pathophysiological Mechanisms Susceptible mentioning
confidence: 99%
“…It should be noted that although most studies indicate that antioxidants protect against oxidative stress and thus extend lifespan (Anisimov et al ., 2011; Niu et al ., 2013) and lead to enhanced exercise capacity (Ji et al ., 1998), recently some reports indicated that antioxidants have no beneficial effects on exercise or are even harmful in high concentrations (Selman et al ., 2013). In addition, although a number of studies have reported that exercise leads to increased longevity (Holloszy, 1998; Navarro et al ., 2004; Barnes, 2015), one study in mice is not in agreement (Garcia‐Valles et al ., 2013). However, the overwhelming preponderance of data in patients support the concept that exercise improves not only healthy lifespan, but also longevity, as it clearly is protective against cardiovascular disease, diabetes, and obesity, all of which are known to reduce lifespan.…”
Section: Discussionmentioning
confidence: 96%
“…The major determinants of cognitive impairment include a history of cigarette smoking, increasing age, and educational level. [7][8][9] Therefore, the inclusion of a matched comparison group, a major strength of this study, might rule out the effect of smoking, age, and education on cognitive functioning. Although we did not match for gender and IQ, there were no significant differences in gender between both groups, and Z-scores were adjusted for educational level, age, and gender.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…[1][2][3][4] The prevalence rates of general cognitive impairment in COPD vary widely, ranging from 5.5% in a large sample of adults with COPD, measured with the Mini-Mental State Examination (MMSE), 5 up to 77.0% in patients with both COPD and hypoxemia, measured with multiple cognitive tests. 6 Increasing age is the most significant determinant of cognitive impairment, 7 besides a history of tobacco smoking 8 and a low educational level. 9 Although the exact pathogenesis of cognitive impairment in COPD remains unknown, vascular-mediated brain pathology, oxidative stress, hypoxemia, systemic inflammation, and comorbidities are proposed pathways to cognitive impairment.…”
Section: Introductionmentioning
confidence: 99%